Drifted catalytic properties of β-lactamases due to unconstrained use of antibiotics (Journal of Bio-Science, 2012)
Context: Antibiotic resistance is an old problem with new face as the rate of infections due to multidrug resistant bacteria is increasing everyday and the number of new antibiotics to overwhelm the problem is becoming smaller. Major mechanism beneath this growing resistance is concomitant with the changes in ?-lactamases catalytic activity and its functional enhancement. Objectives: In ?-lactamases secreting clinical isolates at least 10% are extended-spectrum ?-lactamases (ESBL) that are not even treatable with ?-lactamases inhibitor like clavulanic acids. This implies that the catalytic domains of ?-lactamases have been mutated towards higher pathogenicity. The aim of the present study is to define the changes in ?-lactamases catalytic efficiency against ?-lactam antibiotics and its inhibitors. Materials and Methods: In this research work we have used multiple drug resistant (MDR) strains from surgical site of infections. A rapid method was used for specific detection of bacterial ?-lactamases that uses ?-lactam antibiotics as substrates. In this, the end products (open beta-lactam ring forms) generated after separately incubating substrates with ?-lactamases producing strains. Those end products of antibiotics were highly fluorescent after specific treatment and could be analyzed visually under long-wave UV lamp for efficiency. Results: ?-lactamases secreting strains are variably capable of defending ?-lactam antibiotics. Interestingly, one of the E. coli strain secretes ESBL, this means that the strain is resistant against clavulanic acid. However, the most fascinating fact of the finding is that ideally the ?-lactamases supposed to hydrolyze Penicillin by default but in our isolates, ?-lactamases are not able to hydrolyze penicillin instead they hydrolyze amoxicillin, a derivative which replaced clinical use of penicillin. In addition to that we have identified the presence of New Delhi Metalo- beta- lactamase in one of the clinical isolates. Conclusion: Rate of evolution in microbes is very high. Thus we presume that some of the amino acids in the functional domain of ?-lactamases have been changed respective to extinct use of penicillin whereas it is effective against clinically used other beta lactam antibiotics. DOI: http://dx.doi.org/10.3329/jbs.v19i0.12999 J. bio-sci. 19 37-42, 2011